An overview of the pre-Suppression Society of Jesus in Spain - Manning, Patricia W. (Patricia Walsh) (Brill research perspectives in Jesuit studies., 2020)
"In An Overview of the Pre-suppression Society of Jesus in Spain, Patricia W. Manning offers a survey of the Society of Jesus in Spain from its origins in Ignatius of Loyola's early preaching to the aftereffects of its expulsion. Rather than nurture the nascent order, Loyola's homeland was often ambivalent. His pre-Jesuit freelance sermonizing prompted investigations. The young Society confronted indifference and interference from the Spanish monarchy and outright opposition from other religious orders. This essay outlines the order's ministerial and pedagogical activities, its relationship with women and with royal institutions, including the Spanish Inquisition, and Spanish members' roles in theological debates concerning casuistry, free will, and the Immaculate Conception. It also considers the impact of Jesuits' non-religious writings."--